Rural-Urban Differences in Poverty: An Analysis of Pennsylvania Counties - Alcantara, Angel; Brewer, Stephanie M.; Jozefowicz, James J. (International Journal of Economics and Financial Issues, 2023)
This study examines the determinants of poverty in rural and urban Pennsylvania counties. Economic and demographic characteristics are evaluated in their relation to the poverty rate using panel data from 2000 to 2019 for the 67 Pennsylvania counties. A two-way fixed effects model is estimated to account for unobserved county-specific and time-specific heterogeneity. The results indicate that there are rural-urban differences in the impacts of explanatory variables. In rural Pennsylvania counties, economic factors have significant effects on the poverty rate. The percentage of employment in manufacturing and construction are negatively related to the poverty rate, while the percentage of renters and employment in agriculture are positively related. In contrast, only the percentage of female-headed households has a positive, statistically significant impact in urban counties. Oaxaca (1973) decomposition indicates that structural characteristics in rural counties help mitigate their poverty rates. The results suggest that different policies must be implemented in urban and rural counties to alleviate poverty.